2010
DOI: 10.1111/j.1745-7599.2009.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing heart disease through the vegetarian diet using primary prevention

Abstract: Improved dietary choices can help improve many chronic conditions. Guidelines for proper nutrition within a vegetarian lifestyle are readily accessible to patients and professionals alike. Referral to a dietitian is an appropriate option in primary care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…MRDs are correlated with decreased consumption of harmful levels of animal fats, and increased consumption of protective foods such as fruit, vegetables, legumes, nuts/seeds, and, for some MRDs, fish protein and oils (Cade, Burly, Greenwood, & the UK Women's Cohort Study Steering Group, 2004;Clifton, 2013). As such, balanced MRDs have numerous positive health implications, and are associated with further protective health behaviours such as reduced alcohol and tobacco consumption (American Dietetic Association, 2003;Apostolopoulou, Michalakis, Miras, Hatzitolios, & Savopoulos, 2012;Barnard, Katcher, Jenkins, Cohen, & Turner-McGrievy, 2009;de Lorgeril et al, 1996;McEvoy, Temple, & Woodside, 2012;Phillips, 2005;Rees et al, 2013;Sofi, Abbate, Gensini, & Casini, 2010;Stitcher, Smith, & Davidson, 2010). However, despite the health benefits associated with eating less meat, individuals' beliefs about the ethicality and healthfulness of meat (including consumption of quantity or type) can vary (e.g., Beardsworth & Bryman, 1999;Beardsworth et al, 2002;Dyett, Sabaté, Haddad, Rajaram, & Shavlik, 2013), influencing whether or not they are motivated to engage in MRD.…”
Section: Introductionmentioning
confidence: 95%
“…MRDs are correlated with decreased consumption of harmful levels of animal fats, and increased consumption of protective foods such as fruit, vegetables, legumes, nuts/seeds, and, for some MRDs, fish protein and oils (Cade, Burly, Greenwood, & the UK Women's Cohort Study Steering Group, 2004;Clifton, 2013). As such, balanced MRDs have numerous positive health implications, and are associated with further protective health behaviours such as reduced alcohol and tobacco consumption (American Dietetic Association, 2003;Apostolopoulou, Michalakis, Miras, Hatzitolios, & Savopoulos, 2012;Barnard, Katcher, Jenkins, Cohen, & Turner-McGrievy, 2009;de Lorgeril et al, 1996;McEvoy, Temple, & Woodside, 2012;Phillips, 2005;Rees et al, 2013;Sofi, Abbate, Gensini, & Casini, 2010;Stitcher, Smith, & Davidson, 2010). However, despite the health benefits associated with eating less meat, individuals' beliefs about the ethicality and healthfulness of meat (including consumption of quantity or type) can vary (e.g., Beardsworth & Bryman, 1999;Beardsworth et al, 2002;Dyett, Sabaté, Haddad, Rajaram, & Shavlik, 2013), influencing whether or not they are motivated to engage in MRD.…”
Section: Introductionmentioning
confidence: 95%
“…Es ist zudem bekannt, dass Vegetarismus zu einem normalen Gewicht beitragen kann [28,29]. Bei Erwachsenen mit zu hohem Blutdruck kann darüber hinaus das Essen von Früchten und Gemüse das lipidbedingte kardiovaskuläre Risiko mässigen [30].…”
Section: Zusammenhang Zwischen Nutzung Komplementärer Medizin Und Nieunclassified
“…Epidemiological data suggest that individuals who follow diets rich in fruits and vegetables have a lower risk of CNCD and mortality than those who follow diets poor in vegetables 1 . Several studies have shown a connection between the consumption of meat and hypertension, risk of heart disease, metabolic disorders, and mortality [2][3][4][5][6][7][8][9] . The relationship between food and diseases in groups who follow specific diets, such as vegetarians, have required the attention of scholars.…”
Section: Introductionmentioning
confidence: 99%